COMMUNICATION AND SOCIAL NETWORKS - BARNETT, GEORGE (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Network analysis is a set of research methods for the examination of social structure based on the patterns of the relations among the components (individuals or higher-level social or information systems). In Communication research, this relation is usually the frequency of information exchanged among the components. In other social sciences the relation may be power, conflict, friendship, joint activities or affiliations, shared language and cognitions, or the spread of diseases. Recently, it has been applied to natural systems (biological and physical) as well. This course will: 1) provide an overview of structural and network theory; 2) present methods for the collection of network data; 3) examine a variety of mathematical and statistical indicators or network properties; 4) introduce software (UCINET, MULTINET, GALILEO and CATPAC) for the analysis of social networks; and 5) offer a series of examples of its application from a variety of substantive areas.